The Impact of YouTube and Family on Religiusity Behavior and Pro-Social Behavior of Teenagers in The City of Sidoarjo - Nadhifah Amaliah Putri Rofiva; Ainur Rochmaniah (Kanal: Jurnal Ilmu Komunikasi, 2023)
YouTube social media is one part of changes in technological advances that provide information openly to its users, so that it can indirectly have an impact, especially among teenagers. Given how YouTube's social media is very easy to access by various groups, this research aims to analysis the impact that the use of YouTube and family social media has on religious behavior and pro-social behavior of teenagers, especially in the city of Sidoarjo. This type of research is quantitative with 140 young respondents in Sidoarjo City, which was taken by random sampling technique. The data obtained in this study were obtained from filling out and distributing questionnaires. The research was completed using multiple regression analysis with the SPSS Statistics application. The results of data processing show that the impact of YouTube and family social media on religious behavior in adolescents in Sidoarjo City has a correlation coefficient of 0.695 and a coefficient of determination of 0.483 at a significance of α (0.05). Meanwhile, the impact of social media YouTube and family on pro-social behavior in adolescents in Sidoarjo City has a correlation coefficient of 0.632 and a coefficient of determination of 0.399 at a significance of α (0.05). So it can be concluded that there is an impact of YouTube and family social media on religiosity and prosocial behavior in adolescents in Sidoarjo City.